Ketahanan Nasional Dalam Perspektif Keilmuan Dan Kesejarahan - Sahil, Amirsyah (Jurnal Kajian Stratejik Ketahanan Nasional, 2018)
National resilience studies can be discussed from different perspectives. Since the nature of study is multi-perspective and hence in gaining knowledge requires a multidisciplinary, interdisciplinary and transdisciplinary approach. In its development, the national resilience studies requires a variety of measurement method frameworks, including quantitative data analysis using SPSS, Hierarchical Analysis, Delphi Methods etc. The choice of method depends heavily on the research needs.